Functional Characterization of Serotonin N-Acetyltransferase Genes (SNAT1/2) in Melatonin Biosynthesis of Hypericum perforatum - Zhou, Wen; Yang, Shu; Zhang, Qian; Xiao, Ruyi; Li, Bin; Wang, Donghao; Niu, Junfeng; Wang, Shiqiang; Wang, Zhezhi (Frontiers in Plant Science, 2021)
Hypericum perforatum is a traditional medicinal plant which contains various secondary metabolites. As an active component in H. perforatum, melatonin plays important roles in plant antioxidation, growth, and photoperiod regulation. Serotonin N-acetyltransferase (SNAT) is the key enzyme involved in the last or penultimate step of phytomelatonin biosynthesis. A total of 48 members of SNAT family were screened and analyzed based on the whole genome data of H. perforatum, and two SNAT genes (HpSNAT1 and HpSNAT2) were functionally verified to be involved in the biosynthesis of melatonin. It was found that HpSNAT1 and HpSNAT2 were highly expressed in the leaves and showed obvious responses to high salt and drought treatment. Subcellular localization analysis indicated that these two proteins were both localized in the chloroplasts by the Arabidopsis protoplasts transient transfection. Overexpression of HpSNAT1 and HpSNAT2 in Arabidopsis (snat) and H. perforatum (wild-type) resulted in melatonin content 1.9-2.2-fold and 2.5-4.2-fold higher than that in control groups, respectively. Meanwhile, SNAT-overexpressing Arabidopsis plants showed a stronger ability of root growth and scavenging endogenous reactive oxygen species (ROS). In this study, the complete transgenic plants of H. perforatum were obtained through Agrobacterium-mediated genetic transformation for the first time, which laid a significant foundation for further research on the function of key genes in H. perforatum.